RETRACTED: Psychological and genetic characteristics and strategies of students’ digital behavior in the context of the formation of the digital ecosystem - Denisova Ekaterina; Ermakov Pavel; Kupriyanov Igor; Grishina Anastasia; Shchetinin Alexey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001